LIST OF AVIFAUNA OF THE AREA DE CONSERVACION REGIONAL “BOSQUES DE SHUNTE Y MISHOLLO” (ACR BOSHUMI) - VÁSQUEZ-ARÉVALO, Francisco Alción (2022)
The lack of information on species richness in Amazonian locations is a major problem for biodiversity conservation, especially in regions that are under threat from deforestation. In order to identify the species present in the Regional Conservation Area "Bosques de Shunté y Mishollo" (ACR BOSHUMI) located inthe province of Tocache, San Martin, we carried out field evaluations between 850-2100 meters of altitude, where we applied visual and auditory census techniques as well as the use of mist nets along transects. We categorized the frequency of these species into i) common, ii) uncommon and iii) rare. As a result of these evaluations, we have recorded 201 bird species distributed in 38 families and 15 orders, with the Tyrannidae family emerging as the richest (32 spp.). Our list includes the endemic species for the country, Ramphocelusmelanogaster and Grallaria przewalskii, as well as migratory birds and birds for local consumption. Thus, we conclude that the ACR BOSHUMI protects an important sample of bird diversity in the montane forests and Amazonian lowlands of Peru.